1994
DOI: 10.1111/j.1749-7345.1994.tb00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Feasibility and Risk Analysis of Australian Red Claw Crayfish Cherax quadricarinatus Aquaculture in the Southeastern United States

Abstract: Australian red claw crayfish Cherar guudricurinutus are receiving increased attention from aquaculturists, but have not been extensively investigated in terms of economic feasibility. In this study, research data from small pond experiments were combined with cost and return data to evaluate prospects for commercial production (50 ha scale) in the southeastern United States. Production data were derived from density experiments involving three initial stocking rates: "low" (l/m2), "medium" (3/mf) and "high" (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
0
17
0
3
Order By: Relevance
“…However, because red claw are a subtropical species, culture of red claw in temperate climate ponds is constrained by a growing season that lasts 5–7 mo in length (Medley 1991; Masser and Rouse 1993). Further, red claw juveniles are not readily available in the USA; therefore, producers must purchase these individuals from hatcheries in other countries (Australia or Mexico) and costs can range from $0.40 to $0.50 (US) per juvenile (with transport costs).…”
mentioning
confidence: 99%
“…However, because red claw are a subtropical species, culture of red claw in temperate climate ponds is constrained by a growing season that lasts 5–7 mo in length (Medley 1991; Masser and Rouse 1993). Further, red claw juveniles are not readily available in the USA; therefore, producers must purchase these individuals from hatcheries in other countries (Australia or Mexico) and costs can range from $0.40 to $0.50 (US) per juvenile (with transport costs).…”
mentioning
confidence: 99%
“…Other analyses have examined the feasibility of new species, investments, production systems, or types of farm organization from the perspective of risk. For example, Medley et al (1994) showed that the economic feasibility of producing Australian red claw crawfish Cherax quadricarinatus was sensitive to various risk factors, including the cost of the juveniles stocked, the production of larger crawfish, price, and the length of the growing season. Net present values for shrimp farming investments in Florida were found to be negative, even with price premiums (Clark et al 2010).…”
Section: Engle and Sapkotamentioning
confidence: 99%
“…Another strain group E, which isolated from Orconectes limosus (Kozubíková et al, 2011 Papua New Guinea. Aquaculture and the aquarium trade have both resulted in wide translocations of the species within Australia, Southeast Asia, South Africa, as well as in central and South America (Medley et al, 1994;Williams et al, 2001;de Moor, 2002;Bortolini et al, 2007;Coughran and Leckie, 2007;Ahyong and Yeo, 2007;Belle and Yeo, 2010). Redclaw crayfish was introduced to Taiwan for research and aquaculture purposes in the early 1990s (Lin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%